Etiological characteristics and management of patients with epistaxis in Aksaray (Annals of Medical Research, 2021)
Aim: Epistaxis is a common condition in humans, particularly in patients with hypertension, and is one of the most common presenting symptoms in ear, nose, and throat emergency consultation. The present study aimed to examine the treatment and hospitalization characteristics of the patients who presented with epistaxis in Aksaray city and to propose an optimized and updated protocol.Material and Methods: The present study retrospectively evaluated 758 patients who presented with epistaxis to the Training and Research Hospital in Aksaray between January 2016 and February 2020. The patients were analyzed in terms of age, sex, seasonal characteristics, hospitalization rates, pathogenesis of epistaxis, sites of bleeding, and treatments.Results: The study included 349 females (46.1%) and 409 males (53.9%); mean patient age was 60.9 ± 9.3 years (range: 3–89 years). The most common comorbidity was hypertension (47.3%), and the most common site of bleeding was the anterior region including the Kiesselbach’s plexus (88.2%). Nasal packing (58.5%) and electrocauterization (29.9%) were performed in most cases. The treatment success was defined as no instance of re-visit by the patients to the hospital due to nasal bleeding within 24 h after the procedure; the treatment was successful in 698 patients (92.1%).Conclusion: Most cases of epistaxis are successfully treated using endoscopic electrocauterization on an outpatient basis. Hospitalization is indicated if surgical intervention, posterior packing, or embolization is required and if deterioration of general condition is observed. The present study proposes an updated protocol optimized for the management of epistaxis.
Keywords: Electrocauterization; ENT emergency; epistaxis; hospitalization